(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The study aims to determine the impact of the Economic strand on grade 12 students for perceiving their future careers. The target of this study is limited to grade 12 students who are on the economics strand, while the not related strand is exempted. The main problem is how the home economics strand will help the students perceive their career with the knowledge they have. Not all college has home economics courses because most schools focus on academic tracks. The researchers came up with the solution of figuring out the answer by researching. The research serves as a way to determine the impact of the home economics strand on senior high schools and how they will apply it to their life. The home economics strand is not just about house choirs. It is much more complicated and harder. The students who take the home economics strand can apply it by working in a fast-food restaurant and hotel front liner. This study utilizes the descriptive qualitative method of research. Qualitative research involves collecting and analyzing non-numerical data to understand concepts, opinions, or experiences. The study aims to determine the impact of the Economic strand on grade 12 students for perceiving their future careers. Purposive sampling was utilized in this study, where one group of respondents was composed of the fifty Home Economics Senior High School Students of Bestlink College Philippines. Survey questionnaires were used as research instruments for data collection. The main purpose of this study is to examine the impact of the Home Economics strand thread perceiving future career opportunities of grade 12 students of Bestlink College of the Philippines. An earlier study found that the Home Economics strand facilitates discovering and further developing their resources and capabilities to be used in their personal life and will gain knowledge and practice skills needed by the student. It will give them prior knowledge and be the foundation for the career they will pursue.